Effect of an educational Preventive Program on Asthma Outcomes: a Clinical Trial - fereshteh Mahooti; sedighe Sadat Tavafian (Zanjan University of Medical Sciences and Health Services, 2016)
Background and Objectives: Asthma is a widespread chronic disease. Preventive behaviors can reduce asthma symptoms. The aim of this study was to evaluate the effect of an educational preventive program on asthma outcomes among patients referring to Khoramabad hospitals, Iran in 2013. Materials and Methods: In this semi-experimental study, we allocated the patients into two intervention (n=50) and control (n=50) groups. The participants completed a valid questionnaire designed to assess the preventive behaviors and the disease outcome at two time points of baseline and 2- month follow up of the study. The intervention group received an education program consisting of one 90-minutes face-to-face session and an educational pamphlet. The data were analyzed using the descriptive and analytical statistics in the SPSS. Results: One hundred patients in both groups completed the questionnaire. The mean age was 49.36±13.12 and 45.78±11.92 years old among the intervention and control groups, respectively. After the intervention, the mean score of the preventive behaviors were 50.0±9.45 and 45.68±18.61 in the intervention and control groups, respectively (p<0.038). In addition, patients in the intervention group experienced lower asthmatic symptoms (P<0.04). Conclusion: This study showed that an outpatient educational program could improve preventive behaviors and disease outcome among patients with asthma.